2020
DOI: 10.1111/1475-6773.13583
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of external vs blended facilitation on collaborative care model implementation in slow‐implementer community practices

Abstract: Objective: To evaluate the comparative effectiveness of external facilitation (EF) vs external + internal facilitation (EF/IF), on uptake of a collaborative chronic care model (CCM) in community practices that were slower to implement under low-level implementation support. Study Setting: Primary data were collected from 43 community practices in Michigan and Colorado at baseline and for 12 months following randomization. Study Design: Sites that failed to meet a pre-established implementation benchmark after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 69 publications
(141 reference statements)
0
16
0
Order By: Relevance
“…Given these wide ranging activities, previous work has illustrated the importance of models of external facilitation that go beyond a lone facilitator [5,11,[16][17][18]. Researchers have described the roles and impacts of facilitator dyads, such as in blended external and internal facilitation designs [19][20][21][22][23][24], and mixed discipline facilitator designs [16][17][18]. These models involve sharing and coordinating different functions of facilitation, though manuscripts rarely detail how they work together.…”
Section: Introductionmentioning
confidence: 99%
“…Given these wide ranging activities, previous work has illustrated the importance of models of external facilitation that go beyond a lone facilitator [5,11,[16][17][18]. Researchers have described the roles and impacts of facilitator dyads, such as in blended external and internal facilitation designs [19][20][21][22][23][24], and mixed discipline facilitator designs [16][17][18]. These models involve sharing and coordinating different functions of facilitation, though manuscripts rarely detail how they work together.…”
Section: Introductionmentioning
confidence: 99%
“…For organizational barriers, Facilitation-based on the integrated-Promoting Action on Research Implementation in Health Services (i-PARIHS) [39] frameworkprovides schools with ongoing consultation from an expert in strategic thinking and EBP implementation to garner administrative support, solve logistical challenges, and build community buy-in. In several communitybased cluster-randomized trials, Facilitation has been shown to improve mental health EBP uptake [30,34,[40][41][42][43][44][45] and to be highly cost-effective [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-level implementation strategies targeting CCM determinants can improve implementation outcomes [ 51 , 52 ]. One promising approach is implementation facilitation, a type of interactive assistance designed to overcome barriers and leverage strengths to foster EBP implementation [ 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…These strategies (e.g., mentoring managers to adapt workflows and support/reinforce EBP delivery) are designed to reduce organizational barriers and leverage resources to support EBP integration. Internal facilitation has augmented the impact of external facilitation on uptake in community settings, but not always [ 51 , 53 , 65 , 69 ]. Generally, research has shown benefits of internal facilitation on EBP competencies/fidelity with providers in adult primary care [ 66 , 70 ] and mental health agencies [ 58 , 71 , 72 ].…”
Section: Introductionmentioning
confidence: 99%